Bladder Malakoplakia Simulating Neoplasm in a Young Girl: Report of a Case and Review of Literature - Rabani, Seyed Mohammad Reza; Rabani, Seyed Hossein (Urology Journal, 2019)
Malakoplakia is a granulomatous disorder caused by infectious process. It was described by Von Hanseman in 1901 for the first time and then by Michaelis and Gutman in 1902. Although the most frequent site of involvement is genitourinary tract, various organs have been reported to be affected. The peak age incidence is about 50 years and it is rare in childhood. In this paper we report a case of bladder malakoplakia which to our knowledge is the youngest with isolated bladder malakoplakia that has been reported.